Economics of Smallholder Animal Husbandry in Lalitpur District of Nepal - Sapkota, Rupak; Karmacharya, Roshan (Economic Journal of Development Issues, 2022)
Livestock farming which contributes 11 percent of the total GDP and 32 percent of agriculture GDP is mostly managed by farm household and small enterprise in Nepal. The study aims to analyze the economic rationale of livestock holding using the benefit-cost ratio of livestock farming by the household level and to assess the determinants of dairy cattle herd size in small farm households. The study was conducted in Dalchoki, a ward of Konjyosom rural municipality of Lalitpur district in the months of October and November, 2016. Structured questionnaires were used to collect data from 178 households using census method following the inclusion criteria as least five goat or a cow or a buffalo. Cost items included feeding cost, livestock purchasing cost, labour cost, insemination, veterinary cost, shed and equipment cost whereas benefit items consisted value of milk, live animal and meat and egg, draught power, value of manure among others. Linear regression was employed to examine the determinants of dairy cattle herd size. The results showed positive net benefit from animal husbandry with labor cost excluded and negative net benefit with labour cost included. The regression results showed that landholding size, remittance, net benefit, ethnicity and economically active family members have positive effect in determining size of the number of dairy cattle.